1995
DOI: 10.1056/nejm199503163321101
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Trial of Three Antipneumocystis Agents in Patients with Advanced Human Immunodeficiency Virus Infection

Abstract: In patients with advanced HIV infection, the three treatment strategies we examined have similar effectiveness in preventing P. carinii pneumonia. Strategies that start with trimethoprim-sulfamethoxazole or with high-dose dapsone, rather than aerosolized pentamidine, are superior in patients with fewer than 100 CD4+ lymphocytes per cubic millimeter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
142
0
11

Year Published

1996
1996
2003
2003

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 314 publications
(158 citation statements)
references
References 20 publications
4
142
0
11
Order By: Relevance
“…10 Based on that study and other recent reports comparing dapsone to TMP/SMX, it appears that daily dosing of dapsone is required to provide protection comparable to TMP/SMX prophylaxis. [21][22][23][24][25] (5) Late-onset CMV pneumonia has emerged as an important complication. 26,27 In a prior study, one-third of late viral infections were caused by CMV, and CMV was responsible for 57% of late life-threatening viral infections.…”
Section: Discussionmentioning
confidence: 99%
“…10 Based on that study and other recent reports comparing dapsone to TMP/SMX, it appears that daily dosing of dapsone is required to provide protection comparable to TMP/SMX prophylaxis. [21][22][23][24][25] (5) Late-onset CMV pneumonia has emerged as an important complication. 26,27 In a prior study, one-third of late viral infections were caused by CMV, and CMV was responsible for 57% of late life-threatening viral infections.…”
Section: Discussionmentioning
confidence: 99%
“…If preventive therapy is tolerated, both regimens are more effective in preventing toxoplasmosis than pentamidine, which by itself will not prevent the disease (13). There are only limited data on the use of atovaquone as primary prophylaxis against toxoplasmosis.…”
Section: Review Of Clinical Trialsmentioning
confidence: 99%
“…Even in the era of highly active antiretroviral therapy there remains a substantial morbidity and mortality from PCP in human immunodeficiency virus (HIV)-infected persons (63). The drug of choice for the prophylaxis and treatment of PCP is SXT (19,37,69), which in numerous comparative trials has been demonstrated to have efficacy superior to that of other agents (13,44,53,60,108,110). Despite its efficacy, many patients managed with SXT will experience treatment-limiting side effects such as rash, renal dysfunction, hepatitis, and bone marrow suppression (53,60,108).…”
Section: Review Of Clinical Trialsmentioning
confidence: 99%
“…The recently reported estimated 36 month cumulative risks of PCP were 21% [4] and 22% [23], as compared to 23% in our analysis. Thus, our breakthrough episodes can be regarded as representative and valid cases for analysis of our subject.…”
Section: Discussionmentioning
confidence: 51%
“…These qualities prove to be of growing clinical relevance in the long-term administration, as concurrent medications with its inherent considerable toxicities are frequently indicated in advanced HIV disease. Accordingly, a study comparing regimens for primary prophylaxis with 48 months of observation time reported that 88% of patients on aerosolized pentamidine but only 23% on co-trimoxazole and dapsone, respectively, were still receiving the drug which they were prescribed originally when they completed the study [4].…”
mentioning
confidence: 99%